Thoughts on the Digital Transformation of Teaching in Chinese Higher Education - Huang Jiatao (SHS Web of Conferences)
Higher education institutions have been infiltrated by the technological progress brought about by the Industrial Revolution 4.0, compelling these institutions to undertake a comprehensive digital transformation. Applying digital transformation methods to higher education teaching is an emerging area that has attracted attention in recent times. This paper investigates the current situation and challenges in the implementation process of digital transformation in Chinese higher education teaching. Subsequently, it puts forward coping strategies such as strengthening technical training, optimizing resource integration, innovating teaching models, enhancing data security, and promoting educational equality and inclusiveness, aiming to promote the smooth progress of digital teaching transformation in higher education.